A novel hybrid storage system integrating a packed-bed thermocline tank and a two-tank storage system for concentrating solar power (CSP) plants. (5th January 2016) - Ju, Xing; Xu, Chao; Wei, Gaosheng; Du, Xiaoze; Yang, Yongping
Highlights: A novel hybrid storage system for CSP systems is proposed. The transient thermal performance of the hybrid system under different weathers is numerically investigated. The hybrid system enables the plant to continuously generate power under unfavorable weathers. Frequent charge–discharge of the thermocline tank is avoided in the hybrid system. Abstract: To overcome the inherent shortcomings of the thermocline storage system, a novel hybrid storage system which integrates a big packed-bed thermocline tank and a small two-tank storage system for concentrating solar power (CSP) plants is proposed. Detailed descriptions of the hybrid storage system are presented and four typical operational modes are proposed. A numerical model is developed for the hybrid storage system incorporated in a hypothetical 50 MWe molten-salt solar tower power plant, and the transient thermal performance under different weather conditions is investigated. The results show that the small hot tank has the buffering effect during short-term solar fluctuations, and thus frequent charging–discharging operations of the packed-bed thermocline tank in the hybrid system are avoided which alleviates the thermocline degradation encountered in conventional thermocline storage systems. The overall heat utilization efficiency of the hybrid storage system can also be improved by utilization of waste heat from the in-depth heat discharging process of the thermocline tank. With the proposed hybrid storage system, the CSP plant can be flexibly run to continuously generate constant power even under very unfavorable weathers.